Pengaruh Pengawas Minum Obat Tablet Fe Pada Ibu Hamil Yang Anemia Terhadap Kenaikan Hb di Wilayah Kerja Puskesmas Padang Luar Kab. Agam : The Effect of Iron Tablet Consumption Supervision on Anemic Pregnant Women on the Increase of Hemoglobin Levels in the Working Area of Padang Luar Health Center, Agam Regency - Lusina Novita; Wedya Wahyu; Tut Wuri Handayani (Fakultas Keperawatan Universitas Andalas, 2012)
Anemia is still one of the major health problems in pregnant women in Indonesia. The most common cause of anemia in pregnant women are iron deficient, the impact of iron deficiency in pregnant women can be observed from fetal morbidity and mortality, as well as increased risk of low birth weight. The aim of this study was to determine the effect of Fe tablet medicine supervisor on pregnant women with anemia of Hb increase in work areas of Padang Luar public health center sub province Agam 2012. Design of study was quasi - experiment with